Literacy, imagination and autonomy in House for Mr. Biswas</> - doi: 10.4025/actascilangcult.v34i1.10020 - Bolfarine, Mariana (Acta Scientiarum. Language and Culture, 2011)
The present article tackles the concepts of literacy, imagination and autonomy in A House for Mr. Biswas (1961) by V. S. Naipaul. The novel reveals that the spread of the English language and Englishness became inevitable during British Imperialism since one of the instruments for its propagation was the imposition of the colonizer’s set of values. It will be shown that although limited and detached from the learners’ reality depicted in the narrative, the missionary school education engendered the imagination as a driving force upon which the protagonist, Mr. Biswas, relies in order to achieve his dreams of autonomy. Theory is mostly foregrounded on works by David Slater, Boaventura dos Santos and Diana Brydon.